1966
DOI: 10.2307/3895644
|View full text |Cite
|
Sign up to set email alerts
|

Contour Furrowing, Pitting, and Ripping on Rangelands of the Western United States

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

1981
1981
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 8 publications
1
30
0
Order By: Relevance
“…This decline takes the form of depletion of high fodder value species and their replacement by plants that are less productive, less palatable, and less nutritious than the original plants (Juneidi and Abu-Zanat, 1993). Thus, artificial revegetation is thought to be the remedy for rehabilitation of these degraded rangelands (Branson et al, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…This decline takes the form of depletion of high fodder value species and their replacement by plants that are less productive, less palatable, and less nutritious than the original plants (Juneidi and Abu-Zanat, 1993). Thus, artificial revegetation is thought to be the remedy for rehabilitation of these degraded rangelands (Branson et al, 1966).…”
Section: Introductionmentioning
confidence: 99%
“…Water which does not infiltrate into the soil surface will flow as surface runoff causing soil erosion (Bradford et al, 1987;Remley & Bradford, 1989). Branson et al (1966) reported that soil moisture storage increased by using contour furrowing at 1}1)5 m intervals, and the yield of perennial grasses increased to about 560 kg ha\. In the desert grasslands of southern Arizona, furrowing produced 2)5 times more grass than the adjacent untreated area, while soil moisture storage was 66 mm in the furrowed area compared with only 30 mm in untreated soil (Brown & Everson, 1952).…”
Section: Introductionmentioning
confidence: 99%
“…Some form of surface treatment, such as contour furrowing with check dams (Branson, Miller, and McQueen, 1966) or gouger pitting (Sindelar and others, 1974), may be required for erosion control on slopes steeper than about 10 percent.…”
Section: Soils and Vegetationmentioning
confidence: 99%